Increased Plasma Levels of Nesfatin-1 in Patients with Newly Diagnosed Type 2 Diabetes Mellitus - Zhang, Z.; Li, L.; Yang, M.; Liu, H.; Boden, G.; Yang, G. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Nesfatin-1, which is derived from nucleobindin2 (NUCB2), has been recently identified as a novel satiety regulator. However, its pathophysiological role in humans remains unknown. The aim of the present study was to investigate plasma nesfatin-1 levels and the association between plasma nesfatin-1 levels and various metabolic parameters in humans.74 subjects with newly diagnosed type 2 diabetes mellitus (nT2DM), 73 subjects with impaired glucose tolerance (IGT) and 73 subjects with normal glucose tolerance (NGT) were enrolled in this study. Plasma nesfatin-1 levels were measured by a commercially available enzyme- linked immunosorbent assay.Plasma nesfatin-1 levels were elevated in subjects with both nT2DM and IGT compared to controls (1.91±0.79 and 1.80±0.80 vs. 1.41±0.58 μ g/L, P<0.05 or P<0.01 ). Simple regression analysis showed that in subjects with IGT and nT2DM, plasma nesfatin-1 correlated positively with body mass index (BMI), hemoglobin A1c (HbA1c), fasting blood glucose (FBG), 2 h blood glucose after a glucose load (2hPBG), fasting plasma insulin (FINS) and the homeostasis model assessment of insulin resistance (HOMA-IR). Multivariate logistic regression analysis revealed that plasma nesfatin-1 was significantly associated with IGT and nT2DM, even after controlling for differences in BMI.Plasma nesfatin-1 concentrations were found to be elevated in subjects with both IGT and nT2DM and to be related with several clinical parameters known to be associated with insulin resistance.
Keywords: insulin resistance; type 2 diabetes mellitus; nesfatin-1